THE ABILITY OF CREATIVE THINGKING IN MATHEMATICS - Mimin Ninawati (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
In this artcle, i discuss about the ability of creative thinking in mathematics, including (1) what is meant by the ablity of creative thinking in mathematics, (2) why the ability to think creatively in mathematics is important and what is the reason, (3) how the ability of creative thinking in mathematics applied in the process of learning mathematics so that the ability of creative thinking in mathematics can be owned by students, (4) what mathematical material is suitable for generating students’ ability of creative thinking in mathematics. The method used in this article is discourse analysis, from some articles in various national and international journals. The discussion is presented in the form of description based on the data that is written in the articles. Based on the data presented in these articles, that to create and develop the ability of creative thinking in mathematics, teachers should be able to choose and apply appropriate models and media in the process of learning mathematics, learning process with discussion based model and problem solving.